2017
DOI: 10.1007/s00259-017-3858-2
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA 11 ligand PET imaging in patients with biochemical recurrence after radical prostatectomy – diagnostic performance and impact on therapeutic decision-making

Abstract: ObjectiveTo evaluate the diagnostic performance of [68Ga]Ga-PSMAHBED-CC conjugate 11 positron emission tomography (PSMA-PET) in the early detection of metastases in patients with biochemical recurrence (BCR) after radical prostatectomy (RP) for clinically non-metastatic prostate cancer, to compare it to CT/MRI alone and to assess its impact on further therapeutic decisions.Material and methodsWe retrospectively assessed 117 consecutive hormone-naïve BCR patients who had 68Ga-PSMA 11 PET/CT (n = 46) or PET/MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 29 publications
(40 reference statements)
1
91
0
2
Order By: Relevance
“…Henkenberens et al also reported a significant decrease in PSA serum levels in 29 patients followed up for a similar period, and also treated according to an oligometastatic concept. Grubmüller et al observed a progressive PSA level decrease at 3 and 6 months, however, all study patients were not treated using the same treatment modality. These highly fragmented data on the therapeutic response obtained after treatment based on PSMA PET‐CT results needs to be prospectively explored more broadly.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Henkenberens et al also reported a significant decrease in PSA serum levels in 29 patients followed up for a similar period, and also treated according to an oligometastatic concept. Grubmüller et al observed a progressive PSA level decrease at 3 and 6 months, however, all study patients were not treated using the same treatment modality. These highly fragmented data on the therapeutic response obtained after treatment based on PSMA PET‐CT results needs to be prospectively explored more broadly.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, this is the first study to prospectively explore the impact on PSA levels in patients scanned using 68 Ga-PSMA PET-CT for recurrent PCa ( 14,16 The other studies described a therapeutic impact of 68 Ga-PSMA PET-CT between 28.6% and 61% [9][10][11][12]17,18 Interestingly, Calais et al 18 however, all study patients were not treated using the same treatment modality. These highly fragmented data on the therapeutic response obtained after treatment based on PSMA PET-CT results needs to be prospectively explored more broadly.…”
Section: Discussionmentioning
confidence: 93%
“…Nowadays, [ 68 Ga]Ga‐prostate specific membrane antigen (PSMA)‐11 ([ 68 Ga]Ga‐PSMA‐HBED‐CC; PSMA 11)‐PET has emerged as a promising molecular imaging tool and is used more and more for the staging of PC. It has shown superior performance compared to standard imaging for primary staging and in patients with biochemical recurrence after local therapy with curative intent . Concerning response to therapy in mCRPC patients, to date, two studies have been published.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown superior performance compared to standard imaging for primary staging 9,10 and in patients with biochemical recurrence after local therapy with curative intent. 11 Concerning response to therapy in mCRPC patients, to date, two studies have been published. A study by Seitz et al, 12 showed that the PSMA 11-PET mean standardized uptake value (SUVmean) is accurate for response assessment in mPC patients undergoing systemic therapy with docetaxel.…”
Section: Introductionmentioning
confidence: 99%
“…(4,18,22,23), and detection of disease recurrence after initial treatment with curative intent, e.g. (24)(25)(26)(27). However, in current clinical practice, the high linear attenuation coefficients of the bones in the pelvis and lower abdomen are assumed to be equal to those of soft tissue, which is incorrect.…”
Section: Discussionmentioning
confidence: 99%